The Chora of Metaponto 5 : A Greek Farmhouse at Ponte Fabrizio - Lanza Catti, Elisa (Book collections on Project MUSE., 2014)
"This volume in the Institute of Classical Archaeology's series on rural settlements in the countryside (chora) of Metaponto is a study of the fourth-century BC farmhouse known as Fattoria Fabrizio, located in the heart of the surveyed chora in the Venella valley (at Ponte Fabrizio). This simple structure richly illustrates the life of fourth-century BC Metapontine farmers of modest means. Thorough interpretations of the farmhouse structure in its wider historical and socioeconomic contexts are accompanied by comprehensive analyses of the archaeological finds. Among them is detailed evidence for the family cult, a rare archaeological contribution to the study of Greek religion in Magna Grecia. The entire range of local Greek ceramics has been studied, along with a limited number of imports. Together they reveal networks within the chora and trade beyond it, involving indigenous peoples of southern Italy, mainland Greeks, and the wider Mediterranean world. Along with the studies of traditional archaeological finds, archaeobotanical analyses have illuminated the rural economy of the farmhouse and the environment of the adjacent chora. Abundant Archaic pottery also documents an important occupation, during the first great flowering of the chora in the sixth century BC. This study provides an ideal complement to the four volumes of The Chora of Metaponto 3: Archaeological Field Survey; Bradano to Basento and an eloquent example of hundreds of farmhouses of this date identified throughout the chora by their surface remains alone"--